2021
DOI: 10.1007/s10570-021-03782-1
|View full text |Cite
|
Sign up to set email alerts
|

Highly viscoelastic, stretchable, conductive, and self-healing strain sensors based on cellulose nanofiber-reinforced polyacrylic acid hydrogel

Abstract: Conductive and self-healing hydrogels are among the emerging materials that mimic the human skin and are important due to their probable prospects in soft robots and wearable electronics. However, the mechanical properties of the hydrogel matrix limit their applications. In this study, we developed a physicochemically dual cross-linked chemically modi ed-cellulose nano bers-carbon nanotubes/polyacrylic acid (TOCNF-CNTs/PAA) hydrogel. The TOCNFs acted both as a nano ller and dispersant to increase the mechanica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…Noticeably, the self-healing hydrogels were wholly merged. It is noteworthy that the self-healing time of the tailored self-healing hydrogels is so lower than that of polyacrylic acid-based self-healing structures 40 , 41 , 47 , 48 . This spontaneous phenomenon is originated from diffusion and permeation at fractured interfaces, generated from the molecular dynamics reviving inter- and intramolecular hydrogen bonds, healing cross-links, and leading to more and more entanglements of the polymers 28 , 29 , 31 33 .…”
Section: Resultsmentioning
confidence: 96%
“…Noticeably, the self-healing hydrogels were wholly merged. It is noteworthy that the self-healing time of the tailored self-healing hydrogels is so lower than that of polyacrylic acid-based self-healing structures 40 , 41 , 47 , 48 . This spontaneous phenomenon is originated from diffusion and permeation at fractured interfaces, generated from the molecular dynamics reviving inter- and intramolecular hydrogen bonds, healing cross-links, and leading to more and more entanglements of the polymers 28 , 29 , 31 33 .…”
Section: Resultsmentioning
confidence: 96%
“…It was revealed that the self‐healing efficiency based on tensile strength and strain of the hydrogels with different BNNS‐NH 2 contents were all above 90% and the self‐healing time was only 10 min exhibited highly efficient self‐healing property which is much faster than the published works. [ 38–40 ] Benefiting from the highly efficient self‐healing property, the hydrogel displayed excellent shapeability. The significant feature made the hydrogel enable to shape and reshape easily realizing the recycling.…”
Section: Resultsmentioning
confidence: 99%
“…The broad bands at 2861 cm −1 and 2923 cm −1 originate from the sp3 C-H stretching mode. 37,38 The mechanical properties of the hydrogel were evaluated on a tensile tester. According to the stress-strain curve presented in Figure 2d, the hydrogel showed an elastic deformation upon stretching up to around 1300%.…”
Section: Page 6 Of 23 Ccs Chemistrymentioning
confidence: 99%